Hospital admissions and place of death of residents of care homes receiving specialist healthcare services: A systematic review without meta‐analysis. (17th September 2021) - Buck, Deborah; Tucker, Sue; Roe, Brenda; Hughes, Jane; Challis, David
Abstract: Aim: To synthesize evidence on the ability of specialist care home support services to prevent hospital admission of older care home residents, including at end of life. Design: Systematic review, without meta‐analysis, with vote counting based on direction of effect. Data sources: Fourteen electronic databases were searched from January 2010 to January 2019. Reference lists of identified reviews, study protocols and included documents were scrutinized for further studies. Review methods: Papers on the provision of specialist care home support that addressed older, long‐term care home residents' physical health needs and provided comparative data on hospital admissions were included. Two reviewers undertook study selection and quality appraisal independently. Vote counting by direction of effect and binomial tests determined service effectiveness. Results: Electronic searches identified 79 relevant references. Combined with 19 citations from an earlier review, this gave 98 individual references relating to 92 studies. Most were from the UK (22), USA (22) and Australia (19). Twenty studies were randomized controlled trials and six clinical controlled trials. The review suggested interventions addressing residents' general health needs ( p  < .001), assessment and management services ( p  < .0001) and non‐training initiatives involving medical staff ( p  < .0001) can reduce hospital admissions, while there was also promising evidence for services targeting residents at imminent risk of hospital entry or post‐hospital discharge and training‐only initiatives. End‐of‐life care services may enable residents to remain in the home at end of life ( p  < .001), but the high number of weak‐rated studies undermined confidence in this result. Conclusion: This review suggests specialist care home support services can reduce hospital admissions. More robust studies of services for residents at end of life are urgently needed. Impact: The review addressed the policy imperative to reduce the avoidable hospital admission of older care home residents and provides important evidence to inform service design. The findings are of relevance to commissioners, providers and residents.